Analisis Penerapan "Communciation Skills For Entrepreneur" Pada Keragaman Wirausaha Di Desa Sugihwaras - Ranti Putri, Bella May; Pujianto, Wahyu Eko (Center of Education Journal (CEJou), 2023)
Communication skills for entrepreneurs in a business are one of the most important factors in achieving successful business results. Based on analysis data regarding the application of skills for entrepreneurs in Sugihwaras Village, they do not know in depth about the development of their business, even though it is very important for entrepreneurs to prepare entrepreneurial skills to develop communication skills in entrepreneurship. This study aims to determine the analytical data on the application of communication skills for entrepreneurs in the diversity of entrepreneurs in Sugihwaras Village. Some entrepreneurs are still obsessed with the hypothesis that capital is the main determinant of entrepreneurship. However, this thinking is not quite right, because apart from capital there is a determinant that is actually important in applying entrepreneurial skills, namely having entrepreneurial skills. Entrepreneurial skills include being able to think creatively, being able to manage time management well, having the ability to communicate effectively, being good at managing business strategies, understanding in making decisions, and being brave in taking risks. Through this analytical research, it is hoped that entrepreneurs can further develop how to apply entrepreneurial skills in their business. At first it was assumed that capital was the main determinant in entrepreneurship, entrepreneurs became more aware that the main determinant was capital but that reliable entrepreneurial skills were the main factor in entrepreneurial activity. Then, if you already have communication skills for entrepreneurs, it is hoped that entrepreneurs can be more efficient and effective in running the business they are engaged in. The process of entrepreneurial activity in having good communication skills will create greater opportunities for the final outcome in the process or even risk conditions. The process of communication skills for entrepreneurs can make small businesses born, by formulating step by step communication skills will refer to activities that are definitely needed to build and run a business.